PENGARUH MOTIVASI KERJA, KOMPENSASI, DAN PERILAKU KERJA INOVATIF TERHADAP KINERJA KARYAWAN SEKRETARIAT DAERAH ROKAN HULU, RIAU - Andriyani, Siska; Kirana, Kusuma Chandra; Septyarini, Epsilandri (Jurnal Manajemen Terapan dan Keuangan, 2024)
Abstrak This study objectives to analyze the motivation work, compensation and innovative behavior influnce the employee performance. Using quantitative research with saturated sampling technique with multiple regressionan analysis with classical assumption test to analyse the data with normality, multicollinearity and heteroscedasticity test. The result shows (1) work motivation has a positive effect 0.024 <0.05 significance value, means the greater the work motivation, the better the performance employee. (2) compensation has a positive effect with 0.048 <0.05 significance value, which is the greater the compensation given, the better the employee's performance. (3) innovative work behavior has a positive effect with a significance value of 0.000 <0.05, that mean the better the innovative work behavior implemented, the better the employee's performance. (4) work motivation, compensation and innovative work behavior simultaneously influence employee performance with F value 65,741 and a significance value 0.000 <0.05, which means the more work motivation, compensation and innovative work behavior increases, the better the employee's performance. Kata kunci: work motivation, compensation, innovative work behavior, employee performance